2014
DOI: 10.1097/bot.0b013e31829e6dd0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Locked Plate Fixation of Distal Femur Fractures

Abstract: Prognostic level II. See instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
229
6
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(259 citation statements)
references
References 36 publications
(42 reference statements)
6
229
6
6
Order By: Relevance
“…This contrasts with data from Hoffman et al [14], who reported that 18% of 111 distal femur fractures treated with lateral locking plates without concomitant bone grafting achieved union, indicating that bone grafting with lateral locking plate fixation may be associated with a higher likelihood of fracture union. Although some studies [7,18] have evaluated elements of the internal fixation construct, such as plate length and numbers of screws, these topics remain areas of ongoing study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with data from Hoffman et al [14], who reported that 18% of 111 distal femur fractures treated with lateral locking plates without concomitant bone grafting achieved union, indicating that bone grafting with lateral locking plate fixation may be associated with a higher likelihood of fracture union. Although some studies [7,18] have evaluated elements of the internal fixation construct, such as plate length and numbers of screws, these topics remain areas of ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…Distal femoral nonunions are associated with axial malalignment, chronic pain, loss of ambulatory function, and decreased knee ROM [6,11]. Lateral locking plate fixation has become an accepted standard treatment for the initial fixation of fractures of the distal femur owing to the improved fixation and increased stiffness provided by the fixed angle construct [7,14,18]. Unfortunately, fractures of the distal femur may progress to nonunion despite reduction and fixation with a lateral locking plate [13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of bone graft and bone graft substitute may also play a role in creating an environment for healing. The authors noted the results of two previous studies [1,6] which found that nonunions were treated with a lateral fixed-angle device and bone grafting, achieving similar rates of union.…”
mentioning
confidence: 87%
“…The AAE rates of 44% in PF and 50% in IMN are higher than those cited by other investigators. 11,12 In a retrospective study by Hoffmann et al of 243 surgically treated DF fractures treated with locked PF, 12.6% had surgical complications, the most common of which was deep infection. 13 Initial results from an ongoing trial conducted by Tornetta et al in a randomized trial for 156 patients undergoing PF or IMN for distal femur fractures demonstrated slightly improved functional results for the IMN patients across groups though differences did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and obesity should however not be discounted as risk factors given previous studies finding an increased risk of infection for patients with these characteristics, including those sustaining DF fractures treated with locking plates. 10,11 In addition, it is has been reported that obesity may impact long-term functional outcomes and union rates in DF fractures. 12 Nevertheless, our findings may assuage physician concerns for increased postoperative complications in these patients to some extent.…”
Section: S197mentioning
confidence: 99%